New Approaches to the Study of Esotericism, by Egil Asprem and Julian Strube (eds.) - Albrecht, Jessica A. (Aries - Journal for the Study of Western Esotericism, 2022)
The question “what is esotericism?” has preoccupied the study of esotericism in the last decades. The volume New Approaches to the Study of Esotericism, edited by Egil Asprem and Julian Strube, challenges this question by adding the following part to it: how do we engage with “what is esotericism?” and how does this influence the study of “esotericism”? The editors rightly call for a more thorough engagement with the theoretical and methodological implications of using the term “esotericism” as our field of study as well as the object we study. They argue for a theoretization and critique of our implicit assumptions within the key concepts of the study of esotericism; such are, for instance, the prevalent notion that there is a form of historical “Western esotericism” which subsequently disseminated into the “rest” of the world, as well as the implica- tions this holds for ideas and conceptions of esotericism in relation to white- ness, race, gender, sexuality, and colonialism. Asprem and Strube argue that the continuous use of the “Western” demarcation would reinforce the exclud- ing notion of a “secret knowledge” and uphold the idea that “it” was based on a specific tradition. In order to prevent the study of esotericism from its self- marginalization, the authors of the edited volume unanimously maintain that an interdisciplinary approach and opening towards other fields and disciplines is crucial. Consequently, New Approaches to the Study of Esotericism is a book written by and for a “new generation” (p. 245) of scholars of esotericis